Restriction fragment analysis of the HLA Class II region: Application to tissue transplantation. Issue 1 (February 1989) - Bushell, Andrew; Wood, Kathryn J.
Abstract : Southern blotting and hybridization with locus specific probes is a reliable method for the determination of HLA Class II specificities and in conjunction with several other techniques is providing valuable information on the nature of Class II polymorphisms in man. In terms of the identification of Class II specificities in transplantation however, the advanced nature of DR serology means that DRβ restriction fragment analysis is probably limited only to those situations where serological methods have been unsuccessful. Whether DQ and DP incompatibilities can evoke rejection responses in vivo remains to be fully ascertained although our preliminary data suggest that DQ mismatches probably have little effect upon graft outcome. Restriction fragment analysis is particularly attractive in that in enables reliable retrospective studies to be performed in conjunction with prolonged clinical follow up, and the technique will clearly continue to contribute significantly to our understanding of the importance of these molecules in transplantation.